2019
DOI: 10.3390/su11071843
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Maintenance Cost Analysis for Aged Multi-Family Housing

Abstract: To realize sustainable construction, planning for future maintenance costs is essential. In the case of multi-family housing, various maintenance issues can be expected to appear starting 10 years after completion. Therefore, preventive maintenance must be implemented in a systematic manner to cope with the problems caused by the natural aging of multi-family dwellings and to maintain a sustainable level of quality for the properties. In this study, maintenance costs were investigated for 224 multi-family hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The number of aged buildings is on the increase globally and, in most countries, is accompanied by an increasing number of building defects and associated costs (Park et al , 2019). One of the most pressing tasks is to minimise this rising cost (Au-Yong et al , 2014a, 2016; Forcada et al , 2016; Waziri, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of aged buildings is on the increase globally and, in most countries, is accompanied by an increasing number of building defects and associated costs (Park et al , 2019). One of the most pressing tasks is to minimise this rising cost (Au-Yong et al , 2014a, 2016; Forcada et al , 2016; Waziri, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Lee et al (2018) indicated there is a relative lack of studies providing systemic approaches to reducing defects and their costs. Furthermore, the avenues that would reduce the number of defects and their cost have been getting significant attention from building maintenance stakeholders in several countries (Park et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A building defect is characterised as a "failing or shortcoming in the function, performance, statutory or user requirements of a building and might manifest itself within the structure, fabric, services or other facilities of the affected building" (Watt, 2009). The growth of aged buildings has caused a surge in repair costs associated with building defects (Park, et al, 2019). While the old buildings with defects are typically unsustainable, in major cities, some newly built high-rise buildings have also proved to be unsustainable.…”
Section: Building Defects and Their Impacts On Sustainabilitymentioning
confidence: 99%
“…Therefore, the social aspect of sustainability is immensely affected. On the other hand, the costs allocated for detecting, repairing, and preventing defects are escalating to create a negative impact on economic sustainability (Park, et al, 2019). The degradation of structural elements because of defects, generates waste and emissions making the buildings environmentally unsustainable (Lee, et al, 2018).…”
Section: Building Defects and Their Impacts On Sustainabilitymentioning
confidence: 99%
“…In the process of operating a building, it is difficult to maintain the structures at a safe status all the time, or even in a dangerous state, due to the degradation of materials and damage caused by various harmful factors [1]. Building maintenance has long been recognized globally as a long-term problem in the life cycle of buildings because of the increasing number of deteriorating buildings [2][3][4]. As a part of building operation, it is important to conduct maintenance work, such as repairing failures, replacing components, and discovering construction problems-and solving them in time to ensure normal and safe running status [5].…”
Section: Introductionmentioning
confidence: 99%